2001
DOI: 10.1002/mrm.1274.abs
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative test of the balloon model for BOLD‐based MR signal changes at 3T

Abstract: The aim of this study was to adapt the balloon model for BOLDbased MR signal changes to a magnetic field strength of 3T and to examine its validity. The simultaneous measurement of BOLD and diffusion-weighted BOLD responses was performed. The amplitude of the BOLD peak was found to be similar for all subjects when a short visual stimulus of 6 sec was used. The rise-time to the BOLD peak and the shape and depth of the poststimulus undershoot varied significantly. A fit of the experimental BOLD responses was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
3
20
0
1
Order By: Relevance
“…Therefore, it may be concluded that the poststimulus period had a higher inter-individual variability than the stimulus period in agreement with Mildner et al (2001).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, it may be concluded that the poststimulus period had a higher inter-individual variability than the stimulus period in agreement with Mildner et al (2001).…”
Section: Resultssupporting
confidence: 61%
“…All previous studies that combined fNIRS with another imaging method did not investigate the post-stimulus period of the hemodynamic response. To include that period, we chose a long intertrial interval of 60 s (Mildner et al, 2001). An event-related approach was employed to detect the hemodynamic response to a single trial (Burock et al, 1998;Schroeter et al, 2002Schroeter et al, , 2004c.…”
Section: Introductionmentioning
confidence: 99%
“…A similar windkessel model was proposed by Mandeville et al (1999b) to embody the same concept and provide a biomechanical mechanism for a delayed CBV return to baseline. The balloon model has been refined and compared with experimental data (Feng et al, 2001;Friston, 2002;Friston et al, 2000;Mildner et al, 2001;Obata et al, 2004;Toronov et al, 2003), and some errors in the original parameter estimates were recently corrected (Obata et al, 2004). The model is capable of producing BOLD poststimulus undershoots that match well with experimental data.…”
Section: The Balloon Modelmentioning
confidence: 99%
“…The Friston-Buxton hemodynamic model involves nominally 11 parameters (see Appendix A). When fitting these, some authors (Mildner et al, 2001;Obata et al, 2004) have chosen to fix the values of some parameters (e.g., a, E 0 , V 0 , s 0 , a 1 and a 2 ) on the grounds that these parameters are known approximately from experiments. Others (Friston et al, 2000) have chosen to search on all parameters in light of experimental uncertainties and model assumptions, e.g., the widely cited value a c 0.38 relates f out and CBV only in steady-state (Grubb, 1974) and cannot be assumed to hold generally.…”
Section: 5mentioning
confidence: 99%